Physics textbooks and textbook physics in the nineteenth and twentieth centuries (2017)
This article focuses on physics textbooks and textbook physics in the nineteenth and twentieth centuries, with particular emphasis on developments in France, Germany, Britain, and the United States. It first examines the role that physics textbooks played in the early stages of the professionalization of the history of science before presenting a general overview of the genesis of textbook physics in the nineteenth century. It also looks at major textbooks produced in France and the German states while making some reference to British and American textbooks. Finally, it considers recent scholarship dealing with textbooks in the history of physics. The article shows how our views on textbooks have been shaped by events that have established particular hierarchies between scientific research and science education, and between universities and schools. It argues that the study of textbooks would benefit from greater reflexivity. © Oxford University Press 2013.